KETERSEDIAAN UNSUR HARA TANAMAN SAWI DENGAN PEMUPUKAN BOKASHI DAUN GAMAL PADA TANAH REKLAMASI - Nur Hartanto (DINAMIKA PERTANIAN, 2013)
The purpose of the research was to determine the effect of gamal leaf bokashi application on reclaimed soil to the production of mustard and the plant nutrient availability. The research was conducted at the Experimental Farm of Faculty of Agriculture, University of Mulawarman from August 2001 to January 2012. This study used a randomized block design and treatment was bokashi doses level by 5. Plant parameters measured were plant height, number of leaves, and fresh weight, while the plant tissue parameters analyzed were N, P and K. The results showed that application of gamal leaf bokashi on reclaimed soil had no significantly affect on height and fresh weight of mustard, but had a significant effect on the number of leaves. Giving bokashi in reclaimed soil affected the availability of nutrients on the plant tissue in particular P and K. Mustard plant that contained N, P and K were achieved at the highest dose of 5 tonnes.ha-1. Such the treatments also produced the highest fresh weight.